Dr. Johnson on Shakespeare : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in English at Massey University - Cooper, Dorothy (Massey University, 1980)
The thesis examines Dr Johnson's opinions about Shakespeare's poetic language and wishes to question the view that Johnson, blinded by his concern for linguistic propriety, was incapable of properly appreciating Shakespeare's freedom with the English language. The thesis proceeds by looking at the Notes in Johnson's edition of Shakespeare and by analysing the passages to which they refer, in order to ascertain the real meaning and implications of Johnson's comments. Chapter I outlines the problem. Chapter II notes some points at which Johnson seems unjustly to apply such terms as "harsh" to Shakespeare's poetry. Chapter III looks at the concept of "harshness" in more detail. Chapter IV takes the word "nature" as a focus for Johnson's positive appreciation of Shakespeare's poetic language. Chapter V analyses some Shakespearean passages of the general type for which Johnson, in his Preface to Shakespeare, indicates a preference. Chapter VI considers some Notes in which Johnson specifically praises Shakespeare's poetry. Chapter VII looks at points at which Johnson's adverse comments on the poetry might be argued to be justified.
Keywords: Johnson, Samuel, 1709-1784; Shakespeare, William, 1564-1616; Criticism and interpretation